Isolation and identification of the umami peptides from shiitake mushroom by consecutive chromatography and LC-Q-TOF-MS. (July 2019) - Kong, Yan; Zhang, Li-Li; Zhao, Jing; Zhang, Yu-Yu; Sun, Bao-Guo; Chen, Hai-Tao
Abstract: Umami is critical to the taste of shiitake mushroom. To isolate and identify umami peptides, fractions from hydrolyzed dried shiitake mushroom were separated by ultrafiltration, gel filtration chromatography (GFC), and reversed-phase high-performance liquid chromatography (RP-HPLC). Separations were combined with sensory evaluations (grading and taste dilution analysis) and analysis of electronic tongue, which were used to identify the most umami component in shiitake mushroom. Low-molecular-weight fractions (MW < 3 kDa) have the strongest flavor in the shiitake mushroom hydrolysate. In the 3 subfractions separated from low-molecular-weight fractions (MW < 3 kDa) by GFC, the second subfraction (F2) was selected for RP-HPLC analysis. The first peak (G1) in RP-HPLC was identified by LC-Q-TOF-MS, and 2 tripeptides and 3 dipeptides were identified. The amino acid sequence of these peptides were Gly-Cys-Gly, Glu-Pro-Glu, Cys-Met, Val-Phe, and Gly-Glu. Graphical abstract: Unlabelled Image Highlights: The hydrolysis condition of dried shiitake mushroom was optimized. Five tasty peptides were isolated and identified from dried shiitake mushroom. GCG, GE, and EPE showed umami taste in dried shiitake mushroom.